Plaque-Associated Oligomeric Amyloid-Beta Drives Early Synaptotoxicity in APP/PS1 Mice Hippocampus: Ultrastructural Pathology Analysis - Sanchez-Varo, Raquel; Sanchez-Mejias, Elisabeth; Fernandez-Valenzuela, Juan Jose; De Castro, Vanessa; Mejias-Ortega, Marina; Gomez-Arboledas, Angela; Jimenez, Sebastian; Sanchez-Mico, Maria Virtudes; Trujillo-Estrada, Laura; Moreno-Gonzalez, Ines; Baglietto-Vargas, David; Vizuete, Marisa; et al. (Frontiers in Neuroscience, 2021)
Alzheimer’s disease (AD) is a devastating neurodegenerative disorder characterized by initial memory impairments that progress to dementia. In this sense, synaptic dysfunction and loss have been established as the pathological features that best correlate with the typical early cognitive decline in this disease. At the histopathological level, post mortem AD brains typically exhibit intraneuronal neurofibrillary tangles along with the accumulation of amyloid-beta (Abeta) peptides in the form of extracellular deposits. Specifically, the oligomeric soluble forms of Abeta are considered the most synaptotoxic species. In addition, neuritic plaques are Abeta deposits surrounded by activated microglia and astroglia cells together with abnormal swellings of neuronal processes named dystrophic neurites. These periplaque aberrant neurites are mostly presynaptic elements and represent the first pathological indicator of synaptic dysfunction. In terms of losing synaptic proteins, the hippocampus is one of the brain regions most affected in AD patients. In this work, we report an early decline in spatial memory, along with hippocampal synaptic changes, in an amyloidogenic APP/PS1 transgenic model. Quantitative electron microscopy revealed a spatial synaptotoxic pattern around neuritic plaques with significant loss of periplaque synaptic terminals, showing rising synapse loss close to the border, especially, in larger plaques. Moreover, dystrophic presynapses were filled with autophagic vesicles in detriment of the presynaptic vesicular density, probably interfering with synaptic function at very early synaptopathological disease stages. Electron immunogold labeling showed that the periphery of amyloid plaques, and the associated dystrophic neurites, was enriched in Abeta oligomers supporting an extracellular location of the synaptotoxins. Finally, the incubation of primary neurons with soluble fractions derived from 6-month-old APP/PS1 hippocampus induced significant loss of synaptic proteins, but not neuronal death. Indeed, this preclinical transgenic model could serve to investigate therapies targeted at initial stages of synaptic dysfunction relevant to the prodromal and early AD.